Franz Boas (1858-1942) - Müller-Wille, Ludger (ARCTIC, 1983)
A desire to delve into "the simple relationships between man and land" among the Baffin Island Inuit was the ambitious goal of a 25-year-old German scientist who left Hamburg aboard the Germania on 20 June 1883. The schooner was bound for Kingua Fjord in Cumberland Sound, where the young German would stay for a year, the Germania herself returning home with the German scientific team of the First International Polar Year 1882/83. That voyage - one hundred years ago - marked the beginning of intensive and innovative field work on Inuit geographical perception, social and economic organization, and religious beliefs. In retrospect, this research was also the pivot of an extraordinary scientific career of an influential and farsighted man who shaped modern anthropology in North America - Franz Boas. All his life Boas encouraged rigorous scientific work and international cooperation; moreover, as a conscientious citizen and scientist, he energetically fought cultural and racial prejudices, the implications of which he was keenly aware, having been exposed to them as a Jew in his homeland of Germany. His arctic endeavours, although only a small part of his scientific work, not only advanced the discipline of anthropology in general, but contributed immensely to our knowledge of man-land relations and Inuit culture in the Canadian North. . His curiosity about the Inuit and their arctic environment grew out of the question of how environmental influences on human behaviour affect spatial distribution. . Covering nearly 4000 km on foot, by sled, and by boat, Boas showed no signs of physical fatigue, always pushing himself to the very limit. He vigorously pursued his scientific goals but never neglected to ask for local advice and to adjust to unforeseen circumstances, such as when canine disease left him without dogs for long stretches. With simple instruments he charted the configurations of Cumberland Sound and the east coast of Baffin Island, producing a map that served as a reference into the twentieth century. His ...